SYNTHESIS OF C-METHYL-4,10,16,22-TETRAMETHOXYCALIX[4]ARENE FROM PHENOL USING BF3-METHANOL AS THE CATALYST - Jumina Jumina; Evi Triwulandari; Chairil Anwar (Indonesian Journal of Chemistry, 2005)
C-Methyl 4,10,16,22-tetramethoxycalix[4]arene has been synthesized from phenol. The reaction performed consisted of methylation of phenol, acetylation of methyl phenyl ether, reduction of p-methoxyacetophenone, and cyclization of p-methoxy-(1-hydroxyethyl)benzene to form C-methyl-4,10,16,22-tetramethoxycalix[4]-arene using BF3-methanol as the acid catalyst.  Methylation of phenol was done by reacting phenol with solution of NaOH to generate sodium phenoxide salt. This mixture was strirred at  reflux for 0.5 hours. Dimethyl sulphate was added and the reflux was continued for 2,5 hours. The product obtained was methyl phenyl ether, which was found as  a colorless liquid in 99.0% yield. Acetylation of methyl phenyl ether was carried out in chloroform using acetic anhydride as the acetylating agent and anhydrous aluminium chloride as the catalyst. The addition of acetic anhydride and anhydrous aluminium chloride was done in two portions. The first portion was 0.967 g of acetic anhydride and 1.4 g of anhydrous aluminium chloride. The second portion was 0.54 g of acetic anhydride and 0.6 g of anhydrous aluminium chloride. The product obtained was found as a reddish yellow liquid in 69.6% yield. Reduction of p-methoxyacetophenone as the acetylation product  was  done using NaBH4 in ethanol at reflux for 2.5 hours. From this reaction, p-methoxy-(1-hydroxyethyl)benzene was obtained as a brown viscous liquid in 44.9% yield. Cyclization of p-methoxy(1-hydroxyethyl)benzene was done using BF3-methanol as the acid catalyst for two days at room temperature. The product obtained from this cyclization was found as a brown very viscous liquid in 87.3% yield. Identification of reaction products were carried out using Infra Red (IR) Spectrophotometer, Proton Nuclear Magnetic Resonance (1H NMR) spectrometer and Gas Chromatography-Mass spectroscopy (GC-MS).